Warning Function of Frank’s Sign in Pre-Existing Cardiac Disease Patients: A Case Report - Mingzhe Wang; Yujing Zhang; Jiang Huang; Geping Liao; Wei Qian; Yaofu Zheng; Xiaoping Peng; Jianbing Zhu (Case Reports in Cardiology)
Frank’s sign (FS) refers to a diagonal skin fold between the tragus and the outer edge of the earlobe. FS has been identified as an independent variable in coronary artery disease (CAD). Young patients with FS and previous myocardial infarction are still rarely reported in clinical studies. We report the case of a 49-year-old male smoker and diabetic, with a history of myocardial infarction, who presented to the emergency department due to 2 h typical cardiac chest pain. His urgent electrocardiography (ECG) showed ST elevation, and cardiac biomarkers were elevated after admission. A diagonal earlobe crease (DELC) was observed in physical tests. The preliminary diagnosis considered acute coronary syndrome (ACS). Subsequently, acute coronary artery angiography demonstrated a slit-like contrast defect in the proximal right coronary artery (RCA), with stenosis and occlusion in the distal segment. The percutaneous coronary intervention (PCI) was performed immediately. The patient’s chest pain symptoms were relieved significantly after intervention. Our case indicates that FS should be highly regarded as a routine cardiovascular clinical examination, which can be effortlessly applied and be easily interpreted for screening to suspect the presence of ischemic heart disease. This may set strategies for primary screening in a younger population and prompt early diagnosis and treatment.